Upaya Meningkatan Motivasi Belajar Siswa Fase B Kelas IV Melalui Problem Based Learning (PBL) Pada Materi Aku Pribadi Yang Unik Pendidikan Agama Katolik Dan Budi Pekerti Di SD 20 Sengkabang Muntik Semester Ganjil Tahun Pelajaran 2023/2024 - Benediktus Sutarjo; Lusia Emiliana; Anselmus Yata Mones (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Catholic Religious Education as one of the subjects taught at the basic education level. Religious education here takes a central role in moral education because it is only in the context of religion that a student's life experience can be seen through the lens of faith, being an experience of faith so that what is taught to students about morality will truly take root in the student's heart. This is what needs to be understood by all education actors, especially schools and teachers so that the education carried out in schools really develops students holistically. Students are expected to be skilled in applying it in everyday life, but the reality in the field is that children experience many difficulties, especially the low motivation of students to learn on my unique personal material. One of the efforts to improve student learning outcomes is the Problem Based Learning Method. As a formulation of the problem in this study, can the Problem Based Leraning Method improve the learning outcomes of grade IV Phase B students of SD Negeri 20 Sengkabang Muntik on the material I Am Personal Who is Unique in the odd semester of the 2023/2024 academic year? And how is the application of Problem Based Leraning in improving the learning outcomes of grade IV Phase B students of SD Negeri 20 Sengkabang Muntik on the material I Am Personal Unique odd semester of the 2023/2024 academic year? The purpose of this study was to improve the learning outcomes of grade IV students of SD Negeri 20 Sengkabang Muntik on the material I Am a Unique Person. The subjects in this study were 5 Catholic grade IV students of State Elementary School 20 Sengkabang Muntik. Research activities are carried out for four months starting from the planning stage to the preparation of reports. The research procedure is carried out in four steps, namely, planning, implementation, obsercation and reflection. The data collection techniques used are observation and documentation analysis. The data analysis used is by comparative descriptive techniques that describe a learning technique with the desired results can be achieved.